Kwalifikacja prawna umowy o partnerstwie publiczno-prywatnym w świetle orzecznictwa sądów administracyjnych - Trela, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
This article is acontinuation of Professor Bożena Popowska’s research started in 2006 on private-public partnership PPP. This mentioned research has been conducted due to cooperation between Department of Public Economic Law at Adam Mickiewicz University in Poznań and Department of Public Economic Law at Wrocław University.The author points out that PPP contracts are concluded in many different legal ways. To mention the Act of 9 January 2009 on the licenses on public constructions or services, or the Act of 29 January 2009 on public procurement.The Act of 19 December 2008 on PPP, Art. 4 sec. 3, provides for apossibility of choosing the way of concluding of aPPP contract by the public party. However, that must be conducted in amanner that guarantees free and fair economic competition, transparency and proportionality.The way of choosing private partner depends on the mode of payment for the goods or services. Moreover, it directly determines the means and the scope of control over the PPP contract. Generally, the PPP contracts are overseen by the regular courts. The administrative courts may only verify the choice in terms of the best bid economic efficiency.The article touches upon problems of the definition of PPP and the legal characteristics of the PPP contract as such. In this mentioned area the author presents both the doctrine and the judicature under the 2009 Act on PPP.
Keywords: legal classification; private-public contract; administrative court's judicature